1999
DOI: 10.1046/j.1365-2141.1999.01529.x
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal survey in advanced multiple myeloma: radiographic versus MR imaging survey

Abstract: Summary.In an attempt to compare the sensitivity of bone radiographs and bone marrow magnetic resonance (MR) imaging for bone lesion detection in patients with stage III multiple myeloma (MM) and to evaluate the possible consequences of the replacement of the conventional radiographic skeletal survey (RSS) by an MR survey of the spinal and pelvic bone marrow in these patients, we obtained MR studies of the thoracic and lumbar spine, pelvis and proximal femurs in addition to the conventional RSS (including radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
86
1
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(96 citation statements)
references
References 23 publications
(41 reference statements)
2
86
1
7
Order By: Relevance
“…Therefore, early detection of bone involvement is essential for adequate treatment necessary to prevent associated morbidity. Sensitivity of skeletal surveys in detecting spinal and pelvic lesions is low (42 and 46%, respectively) [14]. In this study, the sensitivity of X-rays in detecting bone lesions was found as 50%, and the levels of bone turnover markers of the patients with positive and negative X-rays were similar.…”
Section: Discussionsupporting
confidence: 44%
“…Therefore, early detection of bone involvement is essential for adequate treatment necessary to prevent associated morbidity. Sensitivity of skeletal surveys in detecting spinal and pelvic lesions is low (42 and 46%, respectively) [14]. In this study, the sensitivity of X-rays in detecting bone lesions was found as 50%, and the levels of bone turnover markers of the patients with positive and negative X-rays were similar.…”
Section: Discussionsupporting
confidence: 44%
“…6 Usually, plasmocytomas produce a monoclonal immunoglobulin in blood, urine, or both (M-component), and cause lytic bone lesions. 12 In 3 ± 7% of the cases, plasmocytoma occurs as a single solitary bone tumour. 3,5,6,8,9,13 Among these, 25 ± 60% occur within the spine, most frequently in the thoracic and lumbar vertebra.…”
Section: Discussionmentioning
confidence: 99%
“…5,8 Staging of plasmocytoma is necessary for optimising therapeutic strategies, and relies on the number of lytic bone lesions, the amount of serum haemoglobin, serum calcium, and monoclonal immunoglobulins. 12 These variables are used because they have been shown to correlate with the tumour mass and survival time. 3 A good prognostic factor of solitary plasmocytomas is the absence of an M-component, found in half of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…48 These imaging modalities have also been explored in defining response to treatment and impact on prognosis; however, they have not yet been incorporated into the IMWG consensus response guidelines. [49][50][51] Positron emission tomography-computed tomography FDG-PET/CT is a functional imaging modality that can show focal osteolysis (CT), focal or diffuse areas of abnormal FDG uptake or CT soft tissue masses (intra-or extramedullary). Although FDG-PET/CT has low spatial resolution (6-8 mm), the combined CT component allows for a direct anatomic correlation of focal FDG uptake and provides high-resolution bone images that are superior to X-ray in detecting lytic bone lesions.…”
Section: Imagingmentioning
confidence: 99%
“…MRI can detect marrow infiltration and epidural extension of myeloma cells, rather than just bony destruction. In a comparison of axial MRI and WBXR, Lecouvet et al 51 found that MRI more frequently detected lytic lesions. However, WBXR was deemed superior, because it demonstrated more appendicular lesions.…”
Section: Imagingmentioning
confidence: 99%